Molecular Identifcation of Lactic Acid Bacteria Producing Antimicrobial Agents from Bakasang, An Indonesian Traditional Fermented Fish Product - Helen Joan Lawalata; Langkah Sembiring; Endang Sutriswati Rahayu (Universitas Gadjah Mada, 2011)
Twenty seven strains of lactic acid bacteria (LAB) were isolated from bakasang, Indonesian traditionalfermented fsh product. In general, LAB have inhibitory activity againts pathogenic bacteria and spoilagebacteria. Screening for antimicrobia activity of isolates were performed with well-diffusion method. Oneisolate that was designed as Pediococcus BksC24 was the strongest against bacteria pathogenic and spoilagebacteria. This strain was further identifed by 16S rRNA gen sequence comparison. Isolates LAB producingantimicrobial agents from bakasang were identifed as Pediococcus acidilactici.